The Experience of Parents in Reducing Children's Autism Tantrums in West Java: A Phenomenological Study - Anni Sinaga; Diana Barsasella; Dian Yuniar Syanti Rahayu; Omay Rohmana; Andi Suhenda; Sugianto Sugianto (Poltekkes Kemenkes Surakarta, 2025)
Background: In autistic children, temper tantrums can occur in association with other challenging behaviors like sleep problems, selective eating, anxiety, irritability, self-harm, and aggression. Families who have adult autistic children experience burdens in their lives. Poor communication and interaction with the child at home provoke an emotional tantrum. This study aims to explore family experiences in reducing children's autistic tantrums through family support. Methods: This phenomenological study involved seven parents of adolescents with autism. The study was carried out over a period of six months, from September 2022 to March 2023, covering the stages of preparation, participant recruitment, in-depth semi-structured interviews, and verbatim transcription. Data were analyzed using Colaizzi’s phenomenological method, which comprised verbatim transcription, identification of significant statements, coding, clustering of themes, and the development of an essential description of the parents’ lived experiences. Results: Six themes were constructed from the study: (1) The process of accepting their children with special needs; (2) Parents' expectations of their children; (3) Internal and external support in reducing autism tantrums; (4) Children join with activities; (5) Enforcement of rules in the family; (6) Family isolation. Conclusion: This study highlights the central role of families in caring for children with autism spectrum disorder (ASD), particularly in managing tantrums. Families apply spiritual values, collaborate among members, and use practical strategies such as providing a safe space, allowing calming time, and redirecting children to meaningful activities. The findings emphasize that family-centered approaches can enhance children’s adaptive abilities and quality of life while reducing caregiver burden.